The Causes of Variation Orders and Their Effects on Cost and Time of Projects in Sulaimani Governorate - M.karim, Karukh Hassan; Ali, Noori; Majeed, Basira (Kurdistan Journal of Applied Research, 2020)
Variation orders are a permanent phenomenon in the construction of projects and industries around the world, and particularly in the province of Sulaymaniyah. Where construction industries suffer from variation orders. It includes an amendment of the initial scope of work as in the awarded contract. This study analyses the causes of variation orders and their effects on cost and time of projects in Sulaimani governorate. This study involves a questionnaire survey to selected 36 causes and 10 effects of variation orders from the perspective of owner, design consultant, and contractors. A total of 223 completed questionnaire sets were returned out of 270 questionnaires distributed among the practitioners. Then the data was analyzed statistically. Also, 40 projects at different construction sectors that constructed during 2007-2013 were investigated by calculating cost and time overrun because of variation orders. The results showed that in Sulaimani governorate the most effective causes of variation orders are owner's financial problems, preparing typical design for different districts, errors and omission in design, desired profitability of contractor and lack of adequate or appropriate site before design stage to construct of project. On the other hand of impacts of variations, the study discovered that top five effects of variation orders on the projects are: schedule overrun, cost overrun, productivity degradation, dispute between contract stockholders and payment delay. Also, all projects affected by cost and time overruns at average of 20 percent of cost and 65.4 percent of time of project.